2010
DOI: 10.1038/aja.2010.82
|View full text |Cite
|
Sign up to set email alerts
|

Control of APN/CD13 and NEP/CD10 on sperm motility

Abstract: Aminopeptidase N (APN/CD13) and neutral endopeptidase (NEP/CD10) are enzymes present in human sperm cells and involved in regulation of sperm motility of noncapacitated spermatozoa. We investigated the involvement of APN/CD13 and NEP/CD10 in motility and in kinematic parameters of human capacitated spermatozoa. Sperm cells isolated by a discontinuous Percoll gradient (40%-80%) followed up by swim-up techniques were incubated with the APN/CD13-specific inhibitor, leuhistin (100 µmol L -1 ), and the NEP/CD10-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 10 publications
1
23
1
Order By: Relevance
“…Although sperm morphology, motility, and total concentration are hypothesized to have the strongest correlation with successful pregnancy, [5][6][7][8] sperm motility may be the most reliable predictor of male factor infertility. [10][11][12] Consistent with this hypothesis, a prospective study designed to evaluate sperm characteristics and the likelihood of pregnancy in infertile couples reported sperm motility and the mean number of morphological abnormalities observed per abnormal spermatozoa (multiple anomalies index) were the best prognostic factors in couples diagnosed with primary infertility. In contrast, age of the male partner and percentage of normal sperm were the best prognostic factors for pregnancy in groups with secondary infertility.…”
Section: Immotile Sperm Are An Important Factor In Male Infertilitymentioning
confidence: 94%
See 4 more Smart Citations
“…Although sperm morphology, motility, and total concentration are hypothesized to have the strongest correlation with successful pregnancy, [5][6][7][8] sperm motility may be the most reliable predictor of male factor infertility. [10][11][12] Consistent with this hypothesis, a prospective study designed to evaluate sperm characteristics and the likelihood of pregnancy in infertile couples reported sperm motility and the mean number of morphological abnormalities observed per abnormal spermatozoa (multiple anomalies index) were the best prognostic factors in couples diagnosed with primary infertility. In contrast, age of the male partner and percentage of normal sperm were the best prognostic factors for pregnancy in groups with secondary infertility.…”
Section: Immotile Sperm Are An Important Factor In Male Infertilitymentioning
confidence: 94%
“…However, each enzyme appears to control different aspects of sperm motility. 10 For example, APN activity is increased in men with asthenozoospermia or necrozoospermia. 17 Subiran et al recently reported that both APN and NEP adversely affect motility as well as the trajectory of human capacitated spermatozoa.…”
Section: Neutral Endopeptidase and Sperm Motilitymentioning
confidence: 99%
See 3 more Smart Citations